EFFECT OF PHOSPHORUS (P) RATES AND WEEDING FREQUENCY ON THE GROWTH AND GRAIN YIELD OF EXTRA EARLY COWPEA (VIGNA UNGUICULATA (L.) WALP) IN THE FOREST – SAVANNA TRANSITION AGRO-ECOLOGICAL ZONE OF SOUTHWEST NIGERIA - Raphael, Adeyemi Olusegun (Journal of Agricultural Sciences (Belgrade), 2020)
Field experiments were conducted at the Teaching and Research Farm of the Federal University of Agriculture, Abeokuta (7o 20’N, 30 23’E) during the 2014 early and late cropping seasons to evaluate the effect of weeding frequency and phosphorus fertilizer application on growth and grain yield of early maturing cowpea variety (Vigna unguiculata ( L.) Walp). The experiment was laid out in a split-plot arrangement fitted into Randomized Complete Block Design with three replications. The main plot consisted of three phosphorus fertilizer rates (0, 15 and 30 P2O5 kg ha-1) while the subplot comprised of five weeding frequencies (no weeding, weed free, hoe weeding at 3 Weeks after Sowing (WAS), hoe weeding at 3 and 6 WAS and weeding at 3, 6 and 9 WAS). The result showed that plots treated with phosphorus fertilizer at 15 kg ha-1 produced the highest number of leaves, tallest plant and highest grain yield during the early and late season trials. Weeding at 3, 6 and 9 WAS during the early season trial gave the highest grain yield compared with other weeding treatments. Unchecked weed infestation reduced yield by 53.10 % and 49.9 % in the early and late seasons respectively compared to the maximum obtained from weed free plots. This study concluded that application of 15 kg P2O5 ha-1 and weed removal at 3, 6 and 9 WAS were effective for effective weed control and optimum grain yield in cowpea production.